Supply Chain Management of PT HM Sampoerna Indonesia - Lee, Cheng-Wen; Ande, Taufiqquddin (Interdisciplinary Social Studies, 2022)
The mission of PT HM Sampoerna is to give adult smokers in Indonesia the best smoking experience possible. One of the reasons for the company's success is the work of supply chain management within PT HM Sampoerna. The goals of this study are to see what factors influence supply chain management techniques in the cigarette sector in Indonesia, with a focus on PT HM Sampoerna Indonesia, to create supply chain management practices in PT HM Sampoerna, to evaluate the efficacy of PT HM Sampoerna's supply chain management, and to identify factors impacting supply chain management in PT HM Sampoerna. This research employs case study research, direct interviews with corporate employees, and secondary approaches such as industry and company websites. The management of the supply chain is generally highly successful. Because they only employ one distributor, PT HM Sampoerna's supply chain management is distinctive. PT Sampoerna gained various benefits that influence the performance of the organization after unifying its supply chain management.